Rozwiązane

2 + 3 ・ x = 14 dla x = 4
L = …………………….
P = ……………………….

2 ・ x – 1 = 19 dla x = 11
L = ……………………..
P = ……………………

4 ・ (x – 2) = 4 + 2 ・x dla x = 6
L = ………………….
P = ……………………

2 ・ x – 1 = 17 – x dla x = 3
L = ……………………..
P = …………………….



Odpowiedź :

Odpowiedź:

2+3*x=14 dla 4

L=2+3*4=2+12=14

P=14

L=P

2*x-1=19 dla x=11

L=2*11-1=22-1=21

P=19

L≠P

4*(x-2)=4+2*x   dla x=6

L=4*(6-2)=4*4=16

P=4+2*6=4+12=16

L=P

2*x-1=17-x   dla x=3

L=2*3-1=6-1=5

P=17-3=14

L≠P

Szczegółowe wyjaśnienie: